2018
DOI: 10.1016/j.jjcc.2018.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Low T3 syndrome improves risk prediction of in-hospital cardiovascular death in patients with acute myocardial infarction

Abstract: LT3S was associated with more severe myocardial injury and increased in-hospital CV mortality in patients with AMI. Furthermore, it improved risk prediction of in-hospital CV death post-AMI when it was added to the TIMI risk score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 26 publications
0
36
1
Order By: Relevance
“…In hospitalized patients with acute heart failure, low FT3 was associated with longer hospital stay and increased ICU admission rate. Low T3 was also a predictor of in-hospital cardiovascular death in patients with acute myocardial infarction [ 4 ] and all-cause mortality in patients with chronic renal failure [ 3 ]. In patients with acute-on-chronic liver failure, reduced TSH, rather than low T3 or low T4, was an independent predictor of death [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In hospitalized patients with acute heart failure, low FT3 was associated with longer hospital stay and increased ICU admission rate. Low T3 was also a predictor of in-hospital cardiovascular death in patients with acute myocardial infarction [ 4 ] and all-cause mortality in patients with chronic renal failure [ 3 ]. In patients with acute-on-chronic liver failure, reduced TSH, rather than low T3 or low T4, was an independent predictor of death [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Decreased serum triiodothyronine (T3) concentration in euthyroid patients, which is termed nonthyroidal illness (NTIS) or euthyroid sick syndrome, is frequently present in critically ill patients. Reduced T3 concentration has been related to mortality in patients with chronic renal failure (CRF) [ 3 ], acute myocardial infarction [ 4 ], and surgical sepsis [ 5 ]. Other studies showed that decreased TSH concentration was an independent predictor of mortality in patients with acute-on-chronic liver failure [ 6 ] or elderly people in community [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Euthyroid sick syndrome (ESS), also known as non-thyroidal illness syndrome, is a transient derangement in thyroid function tests characterized by low T3 levels. ESS is reportedly associated with a higher risk of fatality among critically ill patients admitted with myocardial infarction, sepsis, trauma, and chronic kidney disease [4][5][6][7]. In addition, ICU patients with ESS tend to experience more severe symptoms compared to those with normal thyroid function [8].…”
Section: Introductionmentioning
confidence: 99%
“…The physiological relationship between the cardiovascular system and thyroid function has led to multiple observational studies evaluating the association between hypothyroidism and cardiovascular disease, which have described higher risk of cardiovascular events and mortality in patients with hypothyroidism as compared to those who were euthyroid [4,5]. Low triiodothyronine (T3) has been identified as a prognostic factor for patients with acute myocardial infarction (AMI) associated with increased biomarkers of cardiac injury, decreased left ventricular function, and increased mortality [6,7].…”
Section: Introductionmentioning
confidence: 99%